PENGARUH PENYULUHAN KESEHATAN DAN KESELAMATAN KERJA TERHADAP PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI PADA PETANI(STUDI LITERATURE RIVIEW) - Rifa Shakila; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Use of personal protective equipment is one way to prevent pesticide poisoning. Pesticides can enter the body through the skin and respiratory system. According to WHO, 400,000 to 2 million people worldwide experience pesticide poisoning. The purpose of this study was to determine the effect of health education about the use of personal protective equipment on farmer behavior. This research is a research in the form of Literature Review. Researchers conducted searches on several search engines including: Google Scholar, Pubmed using the keywords "Counseling" AND "Personal Protective Equipment" AND "Farmers". Results: The articles used in this study were 8 articles that met the study requirements and criteria. The results showed that there was an influence of health education about the use of personal protective equipment on farmer behavior. Based on research conducted in a literature review, it can be concluded that there is an influence of counseling on personal protective equipment on farmer behavior